The process of authentication as an appropriation of knowledge through reflection. A diary study on the analysis of print advertisements - Magnini, Simona (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2008)
Authentic materials have long been regarded as a precious source of linguistic input in L2 pedagogy but they have been made the object of a long-term (and on-going) debate starting from the inception of the Communicative Language Teaching approach (CLT) in the 1970s and characterised research in Second Language (L2) pedagogy until this day. As the name suggests, the CLT approach put communication centre-stage and argued that language is best acquired when the learner uses it as a means of communication rather than making it an object of analysis, following this contention authentic texts, that is, texts created for a genuine communicative purpose, were regarded as central to this approach and were exploited communicatively for their content and not for their structure. While there seems to be agreement on the utility of authentic texts in L2 learning, the notion of authenticity and how it promotes language learning is still at the centre of the so-called 'authenticity debate'. A review of the literature shows the notion has been modified according to the predominant pedagogical trend and the recent shift towards learner-centred approaches has progressively homed in on the learner. The literature agrees on the fact that authentic texts are useful in language learning but it is also stressed that it is the learner who activates a dynamic process of 'authentication' in interacting with the text.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin